Pemanfaatan Aplikasi Google Formulir Sebagai Sistem Informasi Untuk Pendataan Pada Kader PKK Kelurahan Ragunan Jakarta Selatan - Eko Setia Budi Eko; Abdul Rahman Kadafi; Eva Zuraidah; Chaerul Bachri; Ipin Sugiyarto; Fitriyani Pramitasari; Afika Kurnia Dewi; Ade Sutrisna; Mochammad Randika; Budi Setiyanto (JPM: Jurnal Pengabdian Masyarakat, 2021)
Karang Taruna is a social organization as a forum and means of developing every member of the community that grows and develops on the basis of awareness and social responsibility from and for the community, especially the younger generation in the region, especially engaged in social welfare efforts. Meanwhile, Karang Taruna membership, hereinafter referred to as Karang Taruna Community, is every member of the community aged 13 (thirteen) years to 45 (forty five) years who resides in the village/kelurahan. Limited understanding of the management of Google Formulas for data collection information systems in the PKK Cadre, Ragunan Village, South Jakarta. Therefore, Nusa Mandiri University carried out Community Service in the form of training on the Use of Google Form Applications at the PKK Cadre of Ragunan Village in South Jakarta. With this training, it can help PKK cadres in Ragunan, South Jakarta in using the Google Form application. After the group is formed, one person is appointed who has the responsibility as chairman. This socialization aims to introduce one of the google doc facilities, namely the google form which can facilitate reporting of activities that have been carried out by the dasawisma of Ragunan village. The result of the implementation of this community service activity is that participants in the activity acquire new knowledge in using Google Forms